Effectiveness, enjoyment, and meaningfulness of a virtual reality gait-based fall prevention exergame in community-dwelling healthy older adults: an interdisciplinary pilot study - Ciemer, Celina; Schott, Nadja; Klotzbier, Thomas Jürgen; Ghellal, Sabiha (Frontiers in Psychology, 2025)
IntroductionFalls are a prevalent health concern among older adults, potentially resulting in substantial physical, psychological, and social ramifications. Interventions aimed at fall prevention require effectiveness, enjoyment, and meaningfulness (EEM). As gait impairments are a key factor in fall risk, integrating natural locomotion and cognitive skills through single- and dual-task training is essential. We developed EXploVR, a fully immersive virtual reality exergame that integrates natural gait and promotes EEM. This interdisciplinary pilot study examined the EEM of EXploVR in healthy, community-dwelling older adults.MethodsForty-six participants were assigned to an intervention or passive control group using a single-blinded, quasi-randomized design. Over three weeks, the intervention group completed two 60-min sessions weekly. Baseline, mid-, and post-assessments included single- and dual-task gait (instrumented normal and tandem walks, counting task), lower limb strength and transitional movement (instrumented Five Times Sit-to-Stand test, 5xSTS), and static postural control (instrumented sway tests). In-game performance (time-to-complete) was recorded. Enjoyment was assessed via the Flow Short Scale (FKS), Physical Activity Enjoyment Scale (PACES-S) and adaptations, and Exergame Enjoyment Questionnaire (EEQ). Meaningfulness was assessed via the Activities-specific Balance Confidence Scales (ABC-6, ABC-8) and custom questions on perceived safety, fear of falling, daily-life integration, emotional challenges, and perceived effectiveness for fall prevention.ResultsData from 32 participants (16 intervention, age = 70.00 ± 3.33 years; 16 control, age = 68.38 ± 5.54 years) were analyzed. Significant improvements were found in walking gait speed (p = 0.019) and tandem gait speed (p = 0.032). Under dual-task conditions, only tandem gait speed improved significantly (p = 0.022). 5xSTS showed a significant interaction for total duration (p = 0.023), while postural sway demonstrated non-significant improvement trends. In-game station completion time improved significantly in 5 of 6 sets (p < 0.05). Enjoyment remained high or increased, and meaningfulness was supported by positive trends in ABC-6 (p = 0.094) and significant gains for ABC-8 (p = 0.026). Custom questions further supported these findings.ConclusionThis study suggests that EXploVR is effective and enjoyable while fostering meaningfulness. Further research with larger samples and extended interventions is needed to confirm long-term effects and daily-life transfer.